2020
DOI: 10.1590/1982-0216/202022217418
|View full text |Cite
|
Sign up to set email alerts
|

Association between severity of the temporomandibular disorder, neck pain, and mandibular function impairment

Abstract: Purpose: to investigate the possible association between the severity of the temporomandibular disorder, cervical pain, and mandibular function impairment. Methods: is a cross-sectional, descriptive study, conducted with 32 individuals with temporomandibular disorder, categorized by degree of severity, according to the Fonseca Index. Using the diagnosis criteria for temporomandibular disorder, the likely etiological factors for the disorder were established, as well as the intensity of the functional disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Hormonal factors are also involved, since estrogen increases susceptibility to painful stimuli by modulating the limbic system. Nunes, et al, (2020) and Viana, et al, (2015) also reported ligament laxity resulting from hormonal changes, and more flexible and less dense joints. Many authors, such as Wiest, et al, (2019) and Weber, et al, (2012), evaluated only female patients, as they are the most affected by TMD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hormonal factors are also involved, since estrogen increases susceptibility to painful stimuli by modulating the limbic system. Nunes, et al, (2020) and Viana, et al, (2015) also reported ligament laxity resulting from hormonal changes, and more flexible and less dense joints. Many authors, such as Wiest, et al, (2019) and Weber, et al, (2012), evaluated only female patients, as they are the most affected by TMD.…”
Section: Discussionmentioning
confidence: 97%
“…It is necessary to be aware of the involvement of psychosocial, emotional, cognitive, and social factors since emotional substrates are present in many TMD cases. Physical examination consists of palpating the TMJ and associated muscles, measuring active movement, and analyzing joint sound (Godinho & Cabral, 2019;Weber, et al, 2012;Nunes, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, there is information on the relationship between cervical spine pain and temporomandibular disorders, which may include biomechanical, neurophysiological, or neuroanatomical aspects [16]. The connection of the cervical spine with the temporomandibular joints shows that they have a direct impact on each other's functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In the scientific literature contains information on the relationship between cervical spine pain and temporomandibular disorders, which may include biomechanical, neurophysiological or neuroanatomical aspects [13]. The connection of the cervical spine with the temporomandibular joints shows that they have a direct impact on each otherʹs functioning.…”
Section: Introductionmentioning
confidence: 99%